PENGARUH EMOTIONAL QUOTIENT, PROFESIONALISME KERJA, DAN GAYA KEPEMIMPINAN TERHADAP PRESTASI KERJA PEGAWAI BPK PROVINSI BALI - I Putu Oka Sucipta; Ni Luh Putu Indiani (Journal of Applied Management Studies, 2023)
This study aimed to determine the influence of emotional quotient, work professionalism, and leadership style on employee work performance. The study population was employees of BPK Bali Province with a sample of 123 respondents. The data analysis technique used multiple linear regression. From the results of the study, it was found that emotional quotient, work professionalism, and leadership style have a positive and significant effect on the work performance of BPK Bali Province employees. This means that the higher the emotional quotient, work professionalism, and the better the leadership style, the higher the employees’ work performance at BPK Bali Province. In the aspect of emotional quotient, BPK Bali Province needs to improve the ability of employees to feel others’ feelings and have competencies that are in accordance with job desc. In the aspect of work professionalism, BPK Bali Province needs to evaluate the ability of employees to work according to the targets (quantity, quality, time) that have been set, and ensure employees complete the work as well as possible on time. In the aspect of leadership style, leaders are expected to have the courage to take risks for the progress of the institution and are willing to accept input.